Hemophagocytic Lymphohistiocytosis Induced by Severe Pandemic Influenza A (H1N1) 2009 Virus Infection: A Case Report - Xiang-Yan Zhang; Xian-Wei Ye; Duan-Xing Feng; Jing Han; Dan Li; Cheng Zhang (Case Reports in Medicine)
After early outbreaks in North America in April 2009, the pandemic influenza A (H1N1) virus spread rapidly around the world, and even some patients developed certain severe complications. We reported one case of hemophagocytic lymphohistiocytosis (HLH) induced by severe pandemic influenza A (H1N1) virus infection. A 17-year-old girl had acute onset of fever, dry cough, rhinorrhea, and sore throat Her family members and close friends also had the similar symptoms. Anti-infection treatment with penicillin was given after 8 days of the onset of symptoms in the local hospital, and her chest radiograph showed consolidation of the left lung. Then, she was sent to the People's Hospital of Guizhou Province in China and endotracheal intubation were underwent on the ninth day for acute hypoxic respiratory failure. She was diagnosed with HLH induced by severe pandemic influenza A (H1N1) 2009 virus. Oseltamivir, steroids, immunoglobulin, and plasmapheresis were given immediately after admission. After being treated in the People's Hospital of Guizhou Province for 16 days, she was discharged. This experience shows that HLH may be a life-threatening complication for severe pandemic influenza A (H1N1) 2009 virus infection and responds well to therapy.